Original article HDR brachytherapy (HDR-BT) combined with stent placement in palliative treatment of esophageal cancer - Kanikowski, Marek; Skowronek, Janusz; Kubaszewska, Magda; Chicheł, Adam; Piotrowski, Tomasz (Journal of Contemporary Brachytherapy, 2009)
Purpose: In the study we present the initial results of palliative treatment using combined methods of HDR-BT and stent insertion in patients with advanced esophagus cancer. Material and methods: Fifty patients were treated in the Great Poland Cancer Center using HDR-BT between June 2001 and December 2005 and they were enrolled into the study. All patients underwent endoscopic insertion of self-expanding, metal, endoesophageal stents owing to blockages in the lumen of the esophagus which excluded brachytherapy. The group included 41 men and 9 women, aged between 44 and 79 years (average 59.3 years). 36 of patients received 3 fractions of HDR once a week of 7.5 Gy, up to total dose of 22.5 Gy, 14 patients received 2 fractions of 7.5 Gy (15 Gy). Results: The average patient observation period was 5.4 months. Complete remission (CR) was observed after 4 weeks in 2 cases (4%), partial remission (PR) in 31 (62%), no remission (NR) was seen in 6 patients (12%) and progression was noted in 11 cases (22%). Complications of brachytherapy for esophageal cancer were observed in 11 patients (22%), ulceration in 1 patient (2%), haemorrhage in 1 patient (2%) and bronchotracheal fistulas in 9 (18%) patients. The average observation period for patients with bronchotracheal fistulas was notably shorter than in remaining patients and amounted 3.5 months. Conclusions: 1. Endoscopic implantation of stents to the lumen of the esophagus provides access to esophagus and, in many cases, allows application of HDR-BT. 2. HDR-BT for advanced esophageal cancer brought relief from dysphagia in most of patients. 3. The combination of the two methods of treatment represents an effective choice for palliative care of this group of patients, with a complication rate similar to observed one in the instance of brachytherapy alone.